Evaluation of the industrial enterprises management systems effectiveness - Bertašius, Donatas (Technological and Economic Development of Economy, 2007)
Today, when the concepts of general quality management science are applied internationally, the certification of quality management systems has become not only the advantage but also the necessity in contemporary competition environment. The conclusions of researches carried out abroad implies the hypothesis that a part of the companies lacks a quality development experience and, as a consequence, are not able to employ all possibilities offered by ISO standards; such standards often become at least partially the attribute of formal administration. The comparison of 2001–2005 year indicators, describing the effectiveness of international standards in organisation of Lithuania with other countries provides the conclusions on the possibilities for a faster and more effective employment of international experience, while working according to the standards of ISO series.Article in Lithuanian.Pramonės įmonių vadybos sistemų efektyvumo vertinimasSantrauka. Diegiant ir įgyvendinant standartizuotas (kokybės, aplinkosaugos, darbuotojų saugos ir sveikatos) vadybos sistemas organizacijose, neefektyviai naudojamos ISO teikiamos standarto galimybės, todėl vadybos sistemos dažnai tampa formalaus administravimo atributu. Atliktas Lietuvos organizacijų, įdiegusių standartizuotas vadybos sistemas, tyrimas ir nustatytas ISO serijos standartų naudojimo efektyvumas. Atlikta 2001–2005 metų Lietuvos ir užsienio valstybių organizacijų standartizuotų vadybos sistemų efektyvumo lyginamoji analizė ir pateiktos išvados apie galimybes greičiau bei efektyviau naudoti tarptautinę patirtį, diegiant ir įgyvendinant standartizuotas vadybos sistemas pagal ISO serijos standartus.Reikšminiai žodžiai: vadybos sistemos, efektyvumas, kokybė, aplinkosauga, lyginamoji analizė.First Published Online: 14 Oct 2010